2019
DOI: 10.1101/597237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NgAgo DNA endonuclease activity enhances homologous recombination in E. coli

Abstract: 15Prokaryotic Argonautes (pAgos) have been proposed as more flexible tools for gene-editing as they do not 16 require sequence motifs adjacent to their targets for function, unlike popular CRISPR/Cas systems. One 17 promising pAgo candidate, from the halophilic archaeon Natronobacterium gregoryi (NgAgo), however, has 18 been subject to intense debate regarding its potential in eukaryotic systems. Here, we revisit this enzyme 19 and characterize its function in prokaryotes. NgAgo expresses poorly in non-halophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…This method may extend to RecA-active strains, if RecA activity can be efficiently inhibited by, for example, expressing RecA inhibitor (36). A recent study also reported NgAgo-assisted recombineering (NgAgo, pAgo from Natronobacterium gregoryi), but the fold change was smaller than 2 and the enhancement of editing was not dependent on NgAgo endonuclease activity (37).…”
Section: Discussionmentioning
confidence: 99%
“…This method may extend to RecA-active strains, if RecA activity can be efficiently inhibited by, for example, expressing RecA inhibitor (36). A recent study also reported NgAgo-assisted recombineering (NgAgo, pAgo from Natronobacterium gregoryi), but the fold change was smaller than 2 and the enhancement of editing was not dependent on NgAgo endonuclease activity (37).…”
Section: Discussionmentioning
confidence: 99%